DIAGNOSIS MODEL PEMBELAJARAN BLENDED LEARNING DENGAN TEKNIK SCAFFOLDING PADA MATA KULIAH MEKANIKA TERAPAN DI PRODI TEKNIKA AKADEMI MARITIM YOGYAKARTA - Ningrum Astriawati; Wegig Pratama (Majalah Ilmiah Bahari Jogja, 2017)
This research is aimed to diagnose the student’s difficulty on Blended Learning model and aimed to get the solution of the problem by using Scaffolding. This research is a type of class action research. The result of the research shows that Blended Learning model by combining 80% of teacher- centered learning and 20% of e-learning program does not seem to be proper to be implemented in maritime academy culture. The proper scaffolding technique to be given is learning model which includes the value of character implementation which is using Co-Prol Learning model. It is proven to be effective not only in developing student’s character but also improving students achievement score. Researcher found that after scaffolding is done by using Co-Prol, the average score of the students is getting increased.